FINANCIAL TRANSACTION SYSTEMS USAGE IN VIETNAM - Binh & 6 Others, Nguyen Thanh (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
In ancient times, non-financial transactions were commonly conducted through systems of credit, in which goods and services were exchanged for a promise of future recompense. The financial systems have evolved from traditional banking to ATM banking, online and mobile transactions. New technologies such as blockchain, which uses a continuously growing list of records, called blocks, which are linked and secured using high-level cryptography In blockchain the transaction records are synchronized. Each copy is identical automatically updated, and immutable. This paper traces the development of the financial transaction system and its evolution in Vietnam.